Statistical Analysis of Logistics Management Impact on Medical Device Indicators in Indonesian Island Clinics - Taupiq, B. Irvan; Razak, Amran; Darmawansyah, Darmawansyah; Arifin, Muhammad Alwy; Rahman, Arsyad; Mallongi, Anwar; Nurhayani, Nurhayani (International Journal of Statistics in Medical Research, 2025)
Background: Public health centers have a strategic role in the implementation of primary health services, to meet minimum service standards. The ASPAK application is used as an instrument for monitoring facilities, infrastructure, and medical devices, but the achievement of medical device indicators in Banggai Laut district is still very low, at 27.87%, which indicates obstacles in the logistics management of medical devices. This study aims to analyze the relationship between logistics management and medical device indicators on the ASPAK Application. Methods: This study employed a quantitative approach with a cross-sectional design. Statistical analysis was conducted using the Pearson Product-Moment Correlation test and multivariate regression to examine the relationship between logistics management and medical device indicators on the ASPAK application across 10 health centers in Banggai Laut District. The research was carried out from September to December 2024, involving a total population of 70 individuals, all of whom were included as the study sample. Result: There is a relationship between logistics management sub-variables and medical device indicators (r=0.583-0.659; p=0.000). Multivariate analysis, planning, and deletion are significantly related (y = 6.877 + 0.437 planning + 0.481 deletion), with an R-square value of 0.638, which means 63.8% of the variation in indicator achievement is explained by the model. Conclusion: Planning and deletion have a positive correlation and are the largest contributors to the fulfillment of the ASPAK medical device indicator. This finding emphasizes the importance of both aspects in supporting indicator achievement.